Encapsulation of Sarcopoterim Spinosum Extract in Zein Perticle by Using Electrospray Method - Süngüç, Ceren; Bayraktar, Oğuz (Izmir Institute of Technology, 2013)
Sarcopoterium spinosum species has valuable and common medicinal plant in the Mediterranean region. The optimum conditions for the extraction of S. spinosum leaves to obtain bioactive extract were investigated using response surface methodology (RSM). Total phenol contents, total antioxidant and antibacterial activities, phenolic composition of S. spinosum extract were studied. The prepared S. spinosum extract showed high antioxidant activity when compared with many other medicinal plants in the literature. It was determined as 3143.5 mmole Trolox per gr dry weight. The phenolic content of S. spinosum extract was examined with High Performance Liquid Chromatography (HPLC). Hyperoside and isoquercetin were detected in S. spinosum extract. Especially, isoquercetin was the major compound in the extract. In addition, the antimicrobial activity of S. spinosum extract was investigated. The extract showed fungicide activity against Candida albicans. S. spinosum extract were encapsulated within zein particle via electrospray method in order to enhance its stability. The effects of process parameters for electrospraying method on the particle morphology and size distribution were extensively investigated. The best process conditions were determined as zein concentration of 5% (w/v) in 70% aqueous ethanol solution, flow rate of 0.3 ml/h and applied voltage of 14 kV depending on narrow size distribution, spherical and smooth particle morphology. The best S. spinosum extract loading was achieved at extract to zein weight ratio of 1:5. The prepared extract loaded zein microparticles showed significant antioxidant activity.
Thesis (Master)--Izmir Institute of Technology, Biotechnology, Izmir, 2013
Includes bibliographical references (leaves: 92-104)
Text in English; Abstract: Turkish and English
xiii, 82 leaves
Keywords: Plant biotechnology; Sarcopoterium; Medicinal plants--Analysis